Larsen Syndrome: A Case Report - Mitra, N; Kannan, Dr Narayanswamy; Kumar, VS; Kavita, G (Journal of Nepal Paediatric Society, 2012)
Larsen syndrome was first described in 1950 by Larsen, Schottstaedt and Bost. This rare inherited disorder is characterized by congenital dislocation of multiple joints along with other anomalies of heart, face, hands and bones. Awareness of this condition and assosciated complications helps in better follow up and management of these patients. Key words: Genu recurvatum; Short stature; Hypodontia; Bifid uvula; Submucosal cleft palate; Cardiac anomaly DOI: http://dx.doi.org/10.3126/jnps.v32i1.5349 J. Nepal Paediatr. Soc. Vol.32(1) 2012 85-87